2020
DOI: 10.1515/sjpain-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of multimodal pain rehabilitation in primary healthcare

Abstract: ObjectivesMultimodal rehabilitation programs (MMRPs) have been shown to be both cost-effective and an effective method for managing chronic pain in specialist care. However, while the vast majority of patients are treated in primary healthcare, MMRPs are rarely practiced in these settings. Limited time and resources for everyday activities alongside the complexity of chronic pain makes the management of chronic pain challenging in primary healthcare and the focus is on unimodal treatment. In order to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…It has been shown to be more effective than care as usual for reducing pain and disability (9) and is considered to be costsaving in terms of, for example, decreasing lost work days and HCU (10,11). Though little studied, a few studies in primary care have reported similar results (12)(13)(14)(15)(16).…”
Section: Jrm-ccmentioning
confidence: 99%
“…It has been shown to be more effective than care as usual for reducing pain and disability (9) and is considered to be costsaving in terms of, for example, decreasing lost work days and HCU (10,11). Though little studied, a few studies in primary care have reported similar results (12)(13)(14)(15)(16).…”
Section: Jrm-ccmentioning
confidence: 99%
“…Eleven outcomes reflecting a BPS approach were evaluated 1 year after IPRP and 10 of these showed significant improvements although ESs were small (0.20-0.49) [92]. A cost-utility analysis indicated that IPRP in primary care was costeffective [93].…”
Section: The 22 Mandatory Outcome Variables In Sqrpmentioning
confidence: 99%
“…The data were collected from primary health care centers in the Norrbotten county of Sweden in 2011-2014 (Calner et al, 2017;Nordin et al, 2016). The studies by Pietilä-Holmner et al and Eklund et al were also both based on the same data; data from 11 primary health care centers in Sweden, collected in 2012-2015 (Eklund et al, 2020;Pietilä-Holmner et al, 2020). Two studies by Mårtensson et al were included, both of which were conducted using the same data, yet reporting different outcomes (Mårtensson et al, 1999;Mårtensson et al, 2004).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies by Mårtensson et al were included, both of which were conducted using the same data, yet reporting different outcomes (Mårtensson et al, 1999;Mårtensson et al, 2004). Nine of the 17 studies included were conducted in Sweden (Calner et al, 2017;Eklund et al, 2020;Gustavsson et al, 2018;Mårtensson et al, 1999;Mårtensson et al, 2004;Nordin et al, 2016;Pietilä-Holmner et al, 2020;Sennehed et al, 2020;Stein & Miclescu, 2013), three in the United States (Dobscha et al, 2009;Seal et al, 2020), two in Canada (Angeles et al, 2013;Barry & Chris, 2019), one in Australia, one in England, and one in the Netherlands (Bults et al, 2023;Clare et al, 2019;Joypaul et al, 2019b; Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%